Expansive and Diverse Phenotypic Landscape of Field Aedes aegypti (Diptera: Culicidae) Larvae with Differential Susceptibility to Temephos: Beyond Metabolic Detoxification. Issue 1 (27th October 2021) - Morgan, Jasmine; Salcedo-Sora, J Enrique; Triana-Chavez, Omar; Strode, Clare
Abstract: Arboviruses including dengue, Zika, and chikungunya are amongst the most significant public health concerns worldwide. Arbovirus control relies on the use of insecticides to control the vector mosquito Aedes aegypti (Linnaeus), the success of which is threatened by widespread insecticide resistance. The work presented here profiled the gene expression of Ae. aegypti larvae from field populations of Ae. aegypti with differential susceptibility to temephos originating from two Colombian urban locations, Bello and Cúcuta, previously reported to have distinctive disease incidence, socioeconomics, and climate. We demonstrated that an exclusive field-to-lab ( Ae. aegypti strain New Orleans) comparison generates an over estimation of differential gene expression (DGE) and that the inclusion of a geographically relevant field control yields a more discrete, and likely, more specific set of genes. The composition of the obtained DGE profiles is varied, with commonly reported resistance associated genes including detoxifying enzymes having only a small representation. We identify cuticle biosynthesis, ion exchange homeostasis, an extensive number of long noncoding RNAs, and chromatin modelling among the differentially expressed genes in field resistant Ae. aegypti larvae. It was also shown that temephos resistant larvae undertake further gene expression responses when temporarily exposed to temephos. The results from the sampling triangulation approach here contribute a discrete DGE profiling with reduced noise that permitted the observation of a greater gene diversity, increasing the number of potential targets for the control of insecticide resistant mosquitoes and widening our knowledge base on the complex phenotypic network of the Ae. aegypti response to insecticides.